Operational Risk of Oil Water Separator (OWS) on Tanker Ships with Failure Mode and Effect Analysis (FMEA) Approach for Prevention of Workplace Accidents and Environmental Pollution - Pratama, Brachmantiyo Rachman; Azhar, Ali; Daryanto, Daryanto (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
The Oil Water Separator (OWS) is a critical system on tankers to prevent marine pollution from oily waste. Its operational failure may cause workplace accidents and violations of MARPOL Annex I, leading to fines and certificate revocation. This study applies the Failure Mode and Effect Analysis (FMEA) method to identify failure modes, analyze causes, and prioritize corrective actions based on the Risk Priority Number (RPN). The analysis revealed several critical failures, including malfunction of the oil content monitor (RPN 336), clogging of the coalescer element (RPN 315), and incomplete closure of the oil discharge valve (RPN 270). Recommendations focus on predictive maintenance, design modifications, and enhanced crew training. The findings confirm that FMEA is effective in shifting OWS maintenance strategies from reactive to risk-based, thereby improving safety and reducing pollution risks.